2020
DOI: 10.1128/msystems.00415-20
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Thaumarchaea with Small Genomes Are Widespread in the Dark Ocean

Abstract: The Thaumarchaeota is a diverse archaeal phylum comprising numerous lineages that play key roles in global biogeochemical cycling, particularly in the ocean. To date, all genomically characterized marine thaumarchaea are reported to be chemolithoautotrophic ammonia oxidizers. In this study, we report a group of putatively heterotrophic marine thaumarchaea (HMT) with small genome sizes that is globally abundant in the mesopelagic, apparently lacking the ability to oxidize ammonia. We assembled five HMT genomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 129 publications
(106 reference statements)
9
57
0
Order By: Relevance
“…The inference of an aerobic ancestor stands in contrast to a recent study (27) that concluded LACAOA arose from an anaerobic ancestor, based on the assumption that all lineages basal to AOA are anaerobic (i.e., non-AOA Thaumarchaeota, Aigarchaeota and Bathyarchaeota). However, most Aigarchaeota and at least two non-AOA Thaumarchaeota (BS4 and pSL12) included in our data set were predicted to be facultative aerobes-the latter being recently further supported by a study reporting metagenome-assembled genomes from the pSL12 lineage with potential for aerobic respiration (22,(41)(42)(43)(44). In our ancestral reconstructions, genes involved in anaerobic metabolisms were inferred as gains in the respective lineages, such as the codH subunits in the ancestor of Bathyarchaeota or nitrate reductase and adenylylsulfate reductase families in Thaumarchaeota BS4 and DS1.…”
Section: Resultssupporting
confidence: 53%
“…The inference of an aerobic ancestor stands in contrast to a recent study (27) that concluded LACAOA arose from an anaerobic ancestor, based on the assumption that all lineages basal to AOA are anaerobic (i.e., non-AOA Thaumarchaeota, Aigarchaeota and Bathyarchaeota). However, most Aigarchaeota and at least two non-AOA Thaumarchaeota (BS4 and pSL12) included in our data set were predicted to be facultative aerobes-the latter being recently further supported by a study reporting metagenome-assembled genomes from the pSL12 lineage with potential for aerobic respiration (22,(41)(42)(43)(44). In our ancestral reconstructions, genes involved in anaerobic metabolisms were inferred as gains in the respective lineages, such as the codH subunits in the ancestor of Bathyarchaeota or nitrate reductase and adenylylsulfate reductase families in Thaumarchaeota BS4 and DS1.…”
Section: Resultssupporting
confidence: 53%
“…We did not detect the 4-hydroxybutyrate/ 3-hydroxypropionate cycle used by ammonia-oxidizing archaea for carbon fixation [78] in any of our samples. However, culturing, DNA stable isotope probing, and MAG data suggest many of these archaea may be mixotrophic or heterotrophic [79][80][81][82][83].…”
Section: Nitrificationmentioning
confidence: 99%
“…Previous studies suggested that some members of Thaumarchaeota are non-AOA and are discovered in diverse environments ( Rinke et al, 2013 ; Weber et al, 2015 ; Hua et al, 2018 ; Aylward and Santoro, 2020 ). Members of non-AOA represent the deepest lineages in the phylogenetic tree of Thaumarchaeota , forming the basal group (Group I.1c) ( Beam et al, 2014 ; Hua et al, 2018 ).…”
Section: Aoa In Estuariesmentioning
confidence: 99%
“…Intriguingly, a group of heterotopic marine Thaumarchaeota , a sister group close to AOA rather than affiliated to the basal group, lacks the ability to oxidize ammonia and to engage in AOA-specific carbon-fixation ( Aylward and Santoro, 2020 ; Reji and Francis, 2020 ). Based on metagenomics data, this group is widespread in marine environments, has smaller genome sizes than AOA, and encode the form III ribulose-bisphosphate carboxylase (RuBisCO) that potentially functions in nucleotide scavenging ( Aylward and Santoro, 2020 ; Reji and Francis, 2020 ). The discovery of this group altered the knowledge of the metabolic diversity of Thaumarchaeota , and established solid connection between the basal non-AOA and AOA groups.…”
Section: Aoa In Estuariesmentioning
confidence: 99%